Conceptual Aerodynamic Studies Of A Small Tailless Unmanned Air Vehicle - Hashim, Afida (2014)
In principle, the tailless model configuration can be equipped with any airfoil as long as the design is compensated with an appropriate combination of some parameter such as aspect ratio, sweep angle and twist. This thesis presents a parametric study of subsonic Tailless UAV conceptual design with some parameter trade off. The usages of three types of airfoils of which are the conventional airfoil, reflex airfoil and symmetrical airfoil in tailless configuration have been studied. The design is divided into three cases which are case 1 (conventional airfoil), case 2 (symmetrical airfoil) and case 3 (reflexed airfoil). All cases are designed to meet the same mission requirement. Analyses of aerodynamic characteristics of three cases have been carried out primarily at cruising speed (18m.s-1) using Computational Fluid Dynamic (CFD) simulation with Spalart-Allmaras turbulence model. The fully structured mesh is employed and grid dependency check had been carried out. The results numerically iterated had been verified and compared to the published data. The lift coefficient, drag coefficient, moment coefficient and lift to drag ratio are plotted, compared and analyzed at different Reynolds number. Generally, by comparison the results of these three cases are consistent with other tailless configurations where it shows similarities in their aerodynamic trends. Though it is realized that conventional airfoil have negative pitching moment, but a moderate amount of pitching moment with proper selections of parameters such as static margin, sweep angle, aspect ratio, and twist will enable the design to obtained a sufficient Cmo. Thus, the sweep angle and the body shape at the center body for case 1 are varied. The results showed a significant improvement in aerodynamic characteristic. The pressure contours and velocity magnitude over tailless configuration were also observed. It may achieve higher aerodynamic efficiency if some multidisciplinary optimization is carried out.